ANALISIS DAN PERANCANGAN SISTEM INFORMASI SURAT KELUAR MASUK DIGITAL PADA TATA USAHA DI SMAN 98 JAKARTA (Current Research in Education: Conference Series Journal, 2023)
The development of information technology is growing so that the design of information systems will continue to be updated. With the existence of an information system design can facilitate users in carrying out an activity that should be done. Not a few information systems in schools that are still considered unfulfilled or even unfit to ease school administrators in processing student data or registered employees. Therefore, it is necessary to design an information system in schools, especially in the field of administration which must have a good information system, especially at SMAN 98 Jakarta where the management of outgoing and incoming letters is still done manually. That way, in this research, research methods are needed in the form of RD to develop a product or update a previous product with a better level of effectiveness than before.